Absolute Versus Relative Fracture Fixation: Impact on Fracture Healing. (March 2018) - Norris, Brent L.; Lang, Gerald; Russell, Thomas A. (Toney); Rothberg, David L.; Ricci, William M.; Borrelli, Joseph
Abstract : Summary: The goals of all orthopaedic surgeons treating fractures are, and will remain, obtaining union of the fracture with a well-aligned and functional limb while minimizing the risk of complications. This requires us to understand how the biomechanical environment of the fracture affects healing and to be able to discern which mechanical environment is preferred over another. Understanding the spectrum of stability imparted by our current surgical devices is paramount to giving our patients the best opportunity to heal and recover from their injury. Gone are the simplistic views of plates and screws being applied for absolute stability and nails and external fixators being applied for relative stability. This review sheds new light on how the use of different implants provides the appropriate stability to encourage fracture healing and limit the risk of complication and loss of function. Abstract : Supplemental Digital Content is Available in the Text.